Changing the quality of living and housing (residential) mobility in Ljubljana. Increase of social instability in larger housing estates? - Matjaž Uršič (Urbani Izziv, 2005)
Most large multi-apartment housing estates in Ljubljana that were mainly built in the period 1960–1985 are in dire need of comprehensive physical renewal and upgrading of utilities. The social-political transformations and events, such as adoption of the new housing law, denationalisation, practical termination of construction of social apartments, increase in construction of profit-based housing and new “actors” in the housing market, are just some of the reasons that strongly affected the decline or slowing down of rehabilitation of large housing estates. Furthermore differences between the living quality in these estates and other (sub)urban areas are becoming evident. In the article we researched, whether slow rehabilitation and diminishment of living qualities are causing the migration of certain population groups and increasing social homogeneity as well as social instability in Ljubljana. First we analysed the changes in living qualities and potential mobility within the wider city area and then we undertook an in-depth analysis of the residential estate Savsko naselje. In conclusion we tried to present some starting points or possibilities for stopping the decline in living quality and accelerating rehabilitation of housing estates.